Dr. Ian Stevenson: A Multifaceted Personality - PASRICHA, SATWANT K. (Journal of Scientific Exploration, 2010)
My association with Dr. Ian Stevenson goes back to October 1973, and I have known him ever since, as a mentor, a guide, a friend, a scientist, and above all a good human being.